2021
DOI: 10.1016/j.rinp.2021.104287
|View full text |Cite
|
Sign up to set email alerts
|

Early prediction of coronavirus disease epidemic severity in the contiguous United States based on deep learning

Abstract: In November 2019, the coronavirus disease outbreak began, caused by the novel severe acute respiratory syndrome coronavirus 2. In just over two months, the unprecedented rapid spread resulted in more than 10,000 confirmed cases worldwide. This study predicted the infectious spread of coronavirus disease in the contiguous United States using a convolutional autoencoder with long short-term memory and compared its predictive performance with that of the convolutional autoencoder without long short-term memory. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 40 publications
(26 reference statements)
0
5
0
Order By: Relevance
“…The studies on the spread of novel coronavirus in the early phase of the pandemic mainly focused on predicting new cases, recovery, and mortality, for global [26], [27] or country-specific scope [28]. Severity analysis of contaminated areas was also a concern for researchers [29]. Risk assessment and mapping for disaster management towards the pandemic were analyzed to prevent wider transmission and reduce the number of cases [30].…”
Section: Topic Hotspotsmentioning
confidence: 99%
See 1 more Smart Citation
“…The studies on the spread of novel coronavirus in the early phase of the pandemic mainly focused on predicting new cases, recovery, and mortality, for global [26], [27] or country-specific scope [28]. Severity analysis of contaminated areas was also a concern for researchers [29]. Risk assessment and mapping for disaster management towards the pandemic were analyzed to prevent wider transmission and reduce the number of cases [30].…”
Section: Topic Hotspotsmentioning
confidence: 99%
“…To predict global or country-based COVID-19 cases [26], [28], [29], [31] Time series COVID-19 dataset ANN-grey wolf optimizer (GWO), marine predators algorithm (MPA)-ANFIS, convolutional auto encoder (CAE) and AL (autoencoder LSTM)-CNN, SIR model 12.…”
Section: Super Learner Ensemblementioning
confidence: 99%
“…But in other cases, it was documented that the symptoms are more severe and individuals can develop pneumonia and necessitates confinement in hospitals. While researchers and health experts continue to study and learn about this disease, it is reported and documented that persons who were not able to survive from the virus had other underlying health issues that predispose them and made the more vulnerable in comparison to the general population such as existence of health comorbidities such as diabetes mellitus, and hypertension (Kao & Perng, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…The virus can be transmitted very quickly from person to person with its high transmission ability. As of March 1, the number of coronavirus cases in the world has exceeded 116 million, and the number of deaths has exceeded 2.5 million (Kao and Perng, 2021). OSHA (Occupational Safety and Health Administration) evaluates healthcare workers in the very high and highrisk groups in terms of the risk of COVID-19 infection (Quinn et al, 2021).…”
Section: Introductionmentioning
confidence: 99%